Measuring the Effect of the Follow-up Evaluation of the Training Exercises for the Tension of Supraspinatus Muscle Animation Injury and Some Physical and Functional Variables - Imad; Ahmed; Ali (University of Thi-Qar Journal, 2020)
The research included one of the injuries that most athletes fusser from while practicing various games which is the injury of Supraspinatus muscle animation of the shoulder joint. The study aimed to prepare training exercises for this type of injury according to the functional and physical aspects of the injured athletes, as well as evaluating these exercises according to different stages of applying. The researchers used the experimental approach and design an experimental group of different stages that is suitable for the problem. The population of the study included the players of shoulder joint injury coursed by musculoskeletal inflammation, premier league participant and participants of the qualifying for the premier league of 2017-2018, in Thi-Qar city. The total of the research community is 12 players. However, the researchers concluded that the praxis of various exercises has a positive effect on the inflammation of supraspinatus muscle animation. Thus, the evaluation of training exercises during different stages showed the amount of improvement through the successful application of these exercises, which reflected on the work of the muscle physically and functionally.